2001
DOI: 10.1053/jhsu.2001.26140
|View full text |Cite
|
Sign up to set email alerts
|

Ulnar nerve excursion and strain at the elbow and wrist associated with upper extremity motion

Abstract: Significant excursion of the ulnar nerve is required for unimpeded upper extremity motion. This study evaluated the excursion necessary to accommodate common motions of daily living and associated strain on the ulnar nerve. The 2 most common sites of nerve entrapment, the cubital tunnel and the entrance of Guyon's canal, were studied. Five fresh-frozen, thawed transthoracic cadaver specimens (10 arms) were dissected and the nerve was exposed at the elbow and wrist only enough to be marked with a microsuture. E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
105
0
7

Year Published

2004
2004
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 165 publications
(122 citation statements)
references
References 16 publications
8
105
0
7
Order By: Relevance
“…This is consistent with human upper limb 16,17 and animal studies. 18 In agreement with earlier work by Daniels et al, 19 ankle dorsiflexion increased strain in the tibial nerve around the ankle (þ3.3%) and resulted in a considerable distal excursion (9.5 mm).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This is consistent with human upper limb 16,17 and animal studies. 18 In agreement with earlier work by Daniels et al, 19 ankle dorsiflexion increased strain in the tibial nerve around the ankle (þ3.3%) and resulted in a considerable distal excursion (9.5 mm).…”
Section: Discussionsupporting
confidence: 91%
“…Although previous studies have demonstrated the usefulness of these transducers to measure strain in nerve trunks, [15][16][17] we used three consecutive repetitions of SRL TIBIAL in five cadavers to calculate the intraclass correlation coefficient [ICC(2,1)] and standard error of measurement (SEM) as measures of reliability for the strain in the tibial nerve around the ankle. The analysis revealed that the strain measurements were reliable in the different position of SLR TIBIAL …”
Section: Strain Measurementsmentioning
confidence: 99%
“…The boundaries of the fibro-osseous cubital tunnel involved in "cubital tunnel entrapment" in the elbow (alternative name for ulnar nerve entrapment at the elbow) are the olecranon and the ulnar collateral ligament laterally, the medial epicondyle with the ulnar nerve sulcus anteriorly, and the cubital tunnel retinaculum (also called Osborn ligament), and the bridging aponeurosis of the two heads of the flexor ulnar carpi muscle (one of the medial epicondyle muscles) medially (21)(22)(23)(24)(25). Anatomic studies explain the effects of repetitive strain on the ulnar nerve at the elbow, and this explanation furthers the understanding of the physiopathology of the disorder (25,26). The association observed between obesity and ulnar nerve entrapment at the elbow can be explained by mechanisms similar to those involved in carpal tunnel syndrome, dealing with the increase of fat and edema in the cubital tunnel.…”
Section: Descatha Et Almentioning
confidence: 99%
“…These findings make sense considering the known pathophysiology of cubital tunnel syndrome. Indeed, whereas the ulnar nerve may be compressed by the thickened confluence of fascia between the two heads of the FCU (and therefore more likely to generate a positive SCT), it is the dynamic tension on the nerve with elbow flexion behind the medial epicondyle that may also contribute to symptomatology [9,11,28,33,37].…”
Section: Discussionmentioning
confidence: 99%